PENGARUH PERANAN CUSTOMER SERVICE DAN KUALITAS PELAYANAN TERHADAP CUSTOMER SATISFACTION DI BPJS KETENAGAKERJAAN CABANG SOLOK - Febsri Susanti; Suci Rahmadhani (LP2M Universitas Bina Bangsa, 2022)
Public awareness about the need for social security in Indonesia is increasing day by day, especially for workers because in order to ensure that they can meet the basic needs of a decent life, financial problems, health problems and maintain the level of welfare. This study aims to determine the influence of the role and quality of customer service. Service to Customer Satisfaction at BPJS Ketenagakerjaan Solok Branch. Determination of the sample is done by using a Stratified Random Sampling sample with the number of respondents as many as 98 workers. Data were collected through questionnaires and then analyzed descriptively and Independent-Sample T-Test with SPSS version 16 program. The results of data analysis showed that Tangibles, Reliability and Responsiveness were the main factors that determine the level of customer satisfaction. While the role of Customer Service, Assurance and Empathy has a not too dominant contribution to customer satisfaction